The hottest topic of the budgetary review: Will the CAP survive? - Andrea Elekes; Péter Halmai (Intereconomics, 2009)
Dalia Grybauskaite, while she was EU Budgetary Commissioner, said that the future financing of the CAP was the hottest topic of the budgetary review. The next months will be decisive as regards the financing of the CAP beyond 2013. Net beneficiaries of the CAP and agricultural interest groups would of course like to maintain the status quo while others would prefer to use the funds for other purposes. When, and how, is the common financing of the CAP justified?
Keywords: 330